(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, the structure and types of vegetable crops, as a result of the study of vegetables, students will learn the biological characteristics and varieties of the main vegetable crops, the modern technology of their cultivation in open and protected lands, and the types, structure, function of protective structures, requirements for the quality of products, purchasing characteristics. acquisition of technologies of transportation and temporary storage of vegetables, new proposals about the timing of planting of Polish crops are determined depending on the weather conditions.